Physical, Chemical, and Sensory Properties of Robusta Coffee Effervescent Tablets Formulated in Various Organic Acids - Umar Hafidz Asy'ari Hasbullah; Miftahul Wahidatun Ni’mah; Endang Is Retnowati; Rini Umiyati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2022)
Coffee effervescent products are an innovation in coffee formulation. The compounds that play a role in effervescent are acids and bases. Type of organic acid give an impact on the effervescent characteristics. This study aimed to examine the effect of type of organic acid on physical, chemical, and sensory properties ofRobusta coffee effervescent tablets. This study used a completely randomized design with three acids in the formulation, namely citric acid, tartaric acid, and malic acid. Samples were analyzed in three replications. Making effervescent tablets was done by compression technique in a mixture of all ingredients according tothe formula. The results showed that different acid had a significant effect on physical and chemical parameters. Malic acid caused a faster effervescent time than citric acid and tartaric acid. Malic acid and tartaric acid tended to lower the pH slightly than citric acid. Malic acid and citric acid tended to produce hardertablets than tartaric acid. However, tartaric acid slightly increased tablets’ brightness (L*) compared to malic acid and citric acid. Tartaric acid and malic acid tended to reduce moisture compared to citric acid. The IC50 value of effervescent with malic acid and tartaric acid was lower than that of citric acid. However, therewas a slight decrease in total phenol in both. Meanwhile, the sensory profiles of tablets and effervescent drinks did not differ due to different acids. The recommended formula was that the effervescent using malic acid had an effervescent time of 166 seconds, hardness 321 N, moisture 8%, IC50 5.5 mg mL-1, total phenol4.2 mg gallic acid equivalent (GAE) g-1, and a drink profile that has the best color, aroma, taste, and runs time